2011
DOI: 10.1007/s00423-011-0808-5
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of theophylline infusions in surgical patients with intra-abdominal hypertension

Abstract: Adenosine receptor antagonism with T following IAH diagnosis resulted in markedly reduced mortality in patients with moderated IAH (<20 mmHg). Theophylline-associated mortality reduction may be related to improved renal perfusion and improved MAP, presumably caused by adenosine receptor blockade. Because this study was not a randomized controlled study, these compelling observations require further multicentric clinical confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…The use of theophylline by counteracting adenosine binding to adenosine receptors has been shown to improve renal function, splanchnic perfusion, and cardiac contractility. The authors concluded that theophylline infusions improved IAH-related mortality in surgical patients by possibly reducing circulating adenosine concentrations [40]. Future studies are warranted to confirm these findings.…”
Section: Theophylline Infusionmentioning
confidence: 89%
“…The use of theophylline by counteracting adenosine binding to adenosine receptors has been shown to improve renal function, splanchnic perfusion, and cardiac contractility. The authors concluded that theophylline infusions improved IAH-related mortality in surgical patients by possibly reducing circulating adenosine concentrations [40]. Future studies are warranted to confirm these findings.…”
Section: Theophylline Infusionmentioning
confidence: 89%
“…Besides the pathophysiological changes in each organ there is also a crucial role of cell abnormalities among which the most important is hypoxia due to the elevated IAP, leading to a significant increase of serum adenosine level [2,3]. During the last few years it was confirmed by numerous studies that hypoxia, trauma and inflammation are trigger factors of adenosine production [2,3,[28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the pathophysiological changes in each organ there is also a crucial role of cell abnormalities among which the most important is hypoxia due to the elevated IAP, leading to a significant increase of serum adenosine level [2,3]. During the last few years it was confirmed by numerous studies that hypoxia, trauma and inflammation are trigger factors of adenosine production [2,3,[28][29][30][31]. Above all, the idea to study the role that adenosine potentially plays in conditions of increased intra-abdominal pressure was provided by previous adenosinerelated experience of the researchers of our working group [2,3,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations